Povos indígenas e a sua relação com o regime jurídico brasileiro como “estranhos de dentro” : da prática de “retirada do meio” ao infanticídio - Uiagumeareu, Liberio (2023)
This dissertation aims to relate indigenous multiculturalism to the practice of “withdrawal from the indigenous environment” with indigenous infanticide. A dialogue between indigenous cultural specificity and the Brazilian legal regime. The research used deductive and bibliographic methods. Even though the Constitution guarantees there are guarantees of constitutional rights of indigenous cultural specificity, there is discussion regarding the right to life and indigenous culture implemented in PL 1057 that is being processed in the National Congress, which aims to create the criminal type of Indigenous Infanticide . This analysis addresses the universalism of human rights, cultural relativism and the restorative state and diatopic hermeneutics. In indigenous history, interventions without any analysis and dialogue with the people to be affected had disastrous results, not unlike, nowadays, the recriminalization of infanticide, without any interaction with indigenous peoples, the main path being intercultural dialogue.